CLONING AND EXPRESSION OF Lb-PROTEASE FROM cDNA CLONE OF FOOT-AND- MOUTH DISEASE VIRUS - Sarkar, Swaroop; Suryanarayana, V.V.S.; Shankar, S.R.Madhan (International Journal of Research -GRANTHAALAYAH, 2017)
Foot-and –Mouth disease virus (FMDV) is a positive sense RNA virus and the genome codes for single polyprotein. The FMDV L protein is located at the N terminus of the polyprotein and is the first gene product released from the nascent polyprotein. The leader L protease which is involved in pathogenesis has two known functions: (i) auto-catalytic removal from the N terminus of the viral polyprotein and (ii) cleavage of the p220 subunit of the eukaryotic initiation factor 4F complex, which helps to shut off host protein synthesis. To explore the role of L protease in FMDV pathogenesis we generated synthetic FMDV genome lacking the L gene. The gene was amplified from an infectious cDNA clone of serotype Asia1. Primers corresponding to L protease were designed based on the sequence available in the data base. An amplified DNA of 546bp was purified and cloned into pET28 cloning vector. The sequence analysis revealed the presence of single Open Reading Frame (ORF) encoding a protein of 173 amino acid residues. The sequence alignment using BLAST search in NCBI gene Bank showed 91% homology with FMDV strain A isolate IND17/77 L protease gene. The recombinant plasmids pETLb was transferred into BL21 (DE3) pLysS cells and the IPTG induced expressed protein of 25 KDa was purified by nickel affinity column as per the manufacturer’s protocol (Sigma, USA). The specificity of the expressed protein in was confirmed by western blotting using convalescent cattle serum/ rabbit anti-bovine horse radish peroxidase conjugate and O-Dianisidine Dihydrochloride substrate.